The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3346/jkms.2017.32.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Air Pollution and Pterygium in Korea

Abstract: We investigated relationships between outdoor air pollution and pterygium in Korean adults. This study includes 23,276 adults in population-based cross-sectional data using the Korea National Health and Nutrition Examination Survey 2008–2011. Pterygium was assessed using slit lamp biomicroscopy. Air pollution data (humidity, particulate matter with aerodynamic diameter less than 10 μm [PM10], ozone [O3], nitrogen dioxide [NO2], and sulfur dioxide levels [SO2]) for 2 years preceding the ocular examinations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…24,28,42 Many other previous studies also found a strong positive association between sun exposure and pterygium as excessive sun exposure causes damage to limbal stem cells by activation of matrix metalloproteinase, which leads to pterygium. [24][25][26]33,42,46 There was also a positive association between wind exposure and the prevalence of pterygium. This finding is supported by the study conducted in Hawaii, which showed that increased risk of exposure to wind while surfing and doing outdoor activities may contribute to pterygium development due to the entrance of airborne debris into the eye.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…24,28,42 Many other previous studies also found a strong positive association between sun exposure and pterygium as excessive sun exposure causes damage to limbal stem cells by activation of matrix metalloproteinase, which leads to pterygium. [24][25][26]33,42,46 There was also a positive association between wind exposure and the prevalence of pterygium. This finding is supported by the study conducted in Hawaii, which showed that increased risk of exposure to wind while surfing and doing outdoor activities may contribute to pterygium development due to the entrance of airborne debris into the eye.…”
Section: Discussionmentioning
confidence: 89%
“…7,15,24 The exposure to environmental factors is also higher in Africa, including Ethiopia but the evidence is scarce on the prevalence of pterygium in this region. 13,[25][26][27][28][29] Therefore, this study aimed to determine the prevalence and associated factors of pterygium among adults in Kolla Diba town. The result of this study will be important for planning and implementing health care services and also act as baseline data for further studies.…”
Section: Introductionmentioning
confidence: 99%
“…The connection between developing a pterygium and level of air pollution is not well studied yet. The population-based study in Korea, which included 23 276 people did not show any association between air pollution and forming or recurrence of pterygium, instead the influence of UV (ultraviolet) light and ageing was observed [9].…”
Section: Review Of the Literature Influence On Conjunctivamentioning
confidence: 88%
“…Accumulating evidence indicates that air pollution has a signi cant impact on cardiovascular-and chronic cardiopulmonary-related morbidity and mortality in China [23][24][25]. Some studies have also shown that air pollution is associated with eye diseases, such as dry eye [26][27], conjunctivitis and pterygium [28].…”
Section: Discussionmentioning
confidence: 99%